THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. PARAMETRIK PRESISI TANGERANG - Prasetiyani, Desi; Sari, Ratna; Kustini, Edang (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to investigate the influence of motivation and discipline on employee performance partially and simultaneously at PT. Parametrik Presisi Tangerang. The method used is a quantitative method with multiple linear regression analysis methods. The population in this study were employees of PT. Parametrik Presisi Tangerang, with a sampling technique using a saturated sample of 65 respondents. The research results show that motivation and discipline have a significant influence on the performance of PT. Parametrik Presisi Tangerang employees. Motivation and discipline together contribute 49.8% to employee performance. Based on these findings, it is recommended for companies to ensure that motivation is met and provide good discipline to improve employee performance.